Education of student youth in the higher educational establishments - Пономарьова, Г. Ф. (Scientific notes of the pedagogical department, 2018)
The essential socio-economic and political transformations in our country, originating from the end of the last century, have changed socio-cultural situation, in which a human personality is formed. Spiritual revival of the Ukrainian nation is possible based on national cultural and historical traditions and universal human values. Therefore, the society and the government have an objective necessity in citizens, who are capable of perception, conservation and development of these traditions and values. The educational system is one of the most important factors in satisfaction of this necessity, the training of generations to reproduce of cultural values. The solution of this problem can not only be achieved by subject, special training of future specialist: education will satisfy modern requirements and will become complete only when its content is defined by educational aims. Therefore, the general problem of higher education in Ukraine is the search of the most effective ways, methods and technologies of students’ education, its preparation for various spheres of society life, for the production sphere. One of the components of this problem is defining of a teacher’s new mission in the modern world.